PROFILE IMPLEMENTATION OF INCLUSIVE EDUCATION IN ELEMENTARY SCHOOL AT KEBUMEN - Chamdani, Muhamad (Universitas Sebelas Maret, 2018)
The purpose of this study is to : (1) the existence of children with special needs in elementary schools that organize inclusive education in Kebumen District, (2) inclusion index achieved in elementary schools that organize inclusive education in Kebumen District, and (3) Implementation of school inclusive education Basic in Kebumen Regency. Inclusion index is obtained through observation in the learning process in class based on 18 indicators. The study was conducted on 10 classes from 4 elementary schools in Kebumen District which organized inclusive education. Inclusive school implementation data were analyzed using an ideal instrument index.The results of the study show that ((1) the number of inclusive elementary school children varies from 1 to 3 children). ((2) The average inclusion index is 31.46 with the ideal inclusion index 54). ((3) Implementation of inclusive education is 227 with an ideal total score of 381).The conclusion of this study is the profile of the implementation of inclusive education in the Kebumen District Primary School shows an average of 59.6% in the medium category.